PENGARUH HALLYU TERHADAP MINAT MASYARAKAT INDONESIA UNTUK BERWISATA KE KOREA SELATAN - Pramita, Yuli; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This reseearch discusses the influence of Hallyu againts the public interest in indonesia to travel to South Korea. Tourism is now a requirement in various communities. Hallyu is the term for spreading the South Korean pop culture in various parts of the world. Hallyu consisting of drama, music, and dance managed to have an impact on the increase in the South Korea tourism. The emergence of Hallyu has become the main attraction for tourists to travel to South Korea.This article was developed using the theory of globalization that is supported by the international community level analysis,where Hallyu emerged as phenomenon that affects the world community en masse.The focus of this study is to see the influence of hallyu that is also growing rapidly in Indonesia. Hallyu becoming known in Indonesia since the 2000s and increasingly popular with the public in 2009. along with the growing popularity of Korean dramas and music, turned out to have an impact on the public interest in Indonesia to travel to South Korea.Keywords: South Korea, Hallyu, Tourism.